Sofrimento psíquico nas organizações: um estudo exploratório junto ao corpo médico de um hospital público no município de Niterói - Leite, Ana Paula Todaro Taveira (2003)
The purpose of this study is to discuss a subject that matters to workers in general, despite colour, sex, age, scholarship or even nationality. Workers with desires and holders of subjectivity, often denied by private or public organizations. The distressing work is in the organizations's daily routine as a psychic burden responsible for physical and psychological diseases, emotional disadjusts, interpersonal conflicts in and outside of the work place, addictions, and urban and family violence. Its polymorphism, allied to its denial by organizations and labor unions confuses and shames the worker, who lives in both solitary and individually. The theory behind this investigation is the studies of the psychic charge of the work developed by Christophe Dejours and his successors. Besides in the specific literature, it was used other studies by psychoanalysts and administration theorists, providing a wide open analysis of the phenomena.